Simbolisme Kematian dalam Antologi Puisi Berbahasa Jawa “Wirid Wulangruh” Karya Nyitno Munajat: The Symbolism of Death in the Javanese Poetry Anthology “Wirid Wulangruh” by Nyitno Munajat - Fatwa Muhammad, Tudung; Ahmadi, Anas; Rizal, Moh. Ahsan Shohifur (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
The study of research into death in Javanese literature is important because this theme does not merely represent the end of life. Death also fosters human spiritual, moral and cultural reflection. However, previous studies have tended to focus on religious and formal aesthetic aspects. The integration of religious thanatological, Sufi and Javanese cosmological perspectives in modern Javanese poetry has not yet been extensively examined. This study aims to uncover the symbolism of death in the poetry anthology Wirid Wulangruh by Nyitno Munajat. The research employs a descriptive-interpretative qualitative approach grounded in Paul Ricoeur’s hermeneutics. The research data consists of two poems on the theme of death, titled “Episode Barzah” and “Yasa Astana Pralaya”. These poems were analysed through the stages of distancing, interpretation, appropriation, and reference. The results of the study indicate that death is constructed as a constructor of meaning, a transitional boundary, transcendent continuity, and an eschatological reality. The symbols of death represent the deconstruction of worldly identity, a spiritual journey towards eternity, and human moral accountability before God. This study reinforces the notion that Javanese Sufi literature functions as a medium for philosophical and spiritual reflection on the nature of human existence.